Changes in the Factors Influencing Forest Floor Terpenoid Emissions During Post-Fire Forest Succession - Zhang-Turpeinen, Huizhong; Aaltonen, Heidi; Tang, Jing ; 0000-0001-7961-8214; Kou, Dan; Kivimäenpää, Minna; Rinnan, Riikka; Pumpanen, Jukka (Journal of Geophysical Research: Biogeosciences, 2025)
The forest floor acts as a source of terpenoid emissions to the atmosphere. These emissions can further impact atmospheric particle formation and impact the atmospheric radiation balance. Climate change escalates wildfire frequency in boreal forests. Wildfires are major disturbances with long-term ecosystem impacts, particularly on the forest floor, significantly influencing terpenoid sources and emissions. This study quantified the post-fire terpenoid emissions from the forest floor and characterized micro-environmental conditions, including abiotic (e.g., air temperature, soil temperature, soil moisture, and light intensity) and biotic factors (ground vegetation characteristics, soil respiration (CO2 fluxes), and soil microbial biomass). We aimed to understand how abiotic and biotic factors affect terpenoid emissions during post-fire succession. Path models revealed direct impacts of ground vegetation on isoprene and monoterpene emissions, while sesquiterpene emissions were mainly regulated by various abiotic factors. Isoprene and monoterpene emissions were influenced by both direct and indirect abiotic factors, mediated through biotic factors like vegetation and soil processes. Effect sizes of the influencing factors varied across forest age classes. Due to the post-fire regrowth of ground vegetation, the impact of temperature on emissions was more pronounced in earlier burned areas than recently burned areas. The influence of soil moisture on terpenoid emissions diminished with forest age. Our findings emphasize the need to identify factors influencing forest floor terpenoid emissions across post-fire succession stages to understand and predict their emission patterns and subsequent impacts on climate.
Keywords: boreal forest; BVOC emission; forest floor; forest succession; wildfire effects